Modifications of Own Mothers’ Milk Fortification Protocol Affect Early Plasma IGF-I and Ghrelin Levels in Preterm Infants. A Randomized Clinical Trial - Agakidou, Eleni (Nutrients, 2019)
The aim was to investigate the effect of two own mother’s milk (OMM) fortification protocols on (a) IGF-I and ghrelin plasma levels at 35 post-conceptional weeks (PCW, T2) and whether this effect is maintained after elimination of the differences in OMM fortification, and (b) growth until 12 months corrected age. Forty-eight OMM-fed preterm infants (GA 24–32 weeks) were randomly allocated to the fixed-fortification (FF) group (n = 23) and the protein-targeting fortification (PTF) group (n = 25) targeting the recommended daily protein intake (PI). Plasma IGF-I and ghrelin were assessed at 35 (T2) and 40 (T3) PCW while growth was longitudinally assessed until 12 months corrected age. PTF group had lower IGF-I and higher ghrelin than FF group at T2, while receiving lower daily protein and energy amounts. PI correlated positively to T2-IGF-I and inversely to T3-ghrelin while energy intake (EI) correlated inversely to T2- and T3-ghrelin. Group and PI were independent predictors of adjusted T2-IGF-I, while group and EI were predictors of adjusted and T2-ghrelin. Growth parameter z-scores were comparable between groups up to 12 months corrected age. Modifications of OMM fortification have a transient effect on early plasma IGF-I and ghrelin levels in preterm infants in a way consistent with the previously recognized protein-energy/endocrine balance, indicating a potential programming effect.